2010
DOI: 10.1016/j.abb.2010.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant and pro-oxidant activities of green tea polyphenols: A role in cancer prevention

Abstract: Green tea (Camellia sinensis) is rich in catechins, of which (−)-epigallocatechin-3-gallate (EGCG) is the most abundant. Studies in animal models of carcinogenesis have shown that green tea and EGCG can inhibit tumorigenesis during the initiation, promotion and progression stages. Many potential mechanisms have been proposed including both antioxidant and pro-oxidant effects, but questions remain regarding the relevance of these mechanisms to cancer prevention. In the present review we will discuss the redox c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
529
1
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(558 citation statements)
references
References 72 publications
15
529
1
13
Order By: Relevance
“…The previous studies of [33,34] reported that GT reduces oxidative stress by virtue of its antioxidant properties thus improving the structural integrity of cell membrane and eventually alleviates the histopathological changes as well as the biochemical perturbations. These results suggest that catechins, epicatechin (EC), epigallocatechin (EGC), epicatechin-3-gallate (ECG), and EGCG could have a direct (antioxidant) or indirect (increase of activity or expression) effect [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies of [33,34] reported that GT reduces oxidative stress by virtue of its antioxidant properties thus improving the structural integrity of cell membrane and eventually alleviates the histopathological changes as well as the biochemical perturbations. These results suggest that catechins, epicatechin (EC), epigallocatechin (EGC), epicatechin-3-gallate (ECG), and EGCG could have a direct (antioxidant) or indirect (increase of activity or expression) effect [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…49,50 In the case of green tea, its polyphenols have been shown to have pro-oxidant activities 46 and thus may actually be mildly toxic, consistent with hormesis as a plausible mechanism of action.…”
Section: -48mentioning
confidence: 99%
“…Flavonoids are polyphenolic compounds that can be found in dietary components such as food products, beverages and herbal medicines with different health benefits shown in a large number of studies [13] . Most flavonoids have an antioxidant activity [14,15] .…”
Section: Introductionmentioning
confidence: 99%